Conflits Fonciers Et Problématique De Développement Rural Dans La Sous-Préfecture De Mongo, Région Du Guéra (Tchad) - Alladjaba, Moussa; Tchekote, Hervé (European Scientific Journal, ESJ, 2018)
Located in the Guéra region in central Chad, the Mongo Sub-Prefecture is the scene of recurring conflicts related to the occupation and exploitation of the land. While the phenomenon is neither new nor specific to this part of the country, the scale it has taken in recent years makes it a worrying subject. This land conflicts are driven by a multitude of actors with traditional authorities, agricultural producers and the urban elite at the center. They are fuelled by the fact that the legal land tenure system, set up first by the colonial authority and then renewed by the Chadian authorities, has never been a reality in rural areas. To conduct the study the questionnaire survey was conducted from a sample of 106 households. Subsequently, semi-structured interviews supplemented the information collected through the questionnaires. The results reveal not only a pluralism of norms whose contradiction in implementation is inevitably conflicting, but also and above all the actors’ play around rural land, with a multitude of conflicts whose impact is strongly felt by populations, both in terms of agricultural or pastoral production, and in terms of trade and social cohesion. At the end of the study, it turns out that the population largely ignores the laws governing the land. The result is a pluralism of norms, but the customary rules are preponderant. This determines several modes of access and use of the land.